Physical Condition Level of Female Volleyball Athletes Club Pekanbaru Pertamina Energi: Tingkat Kondisi Fisik Atlet Bola Voli Puteri Club Pekanbaru Pertamina Energi - Seyla Mouren Zeptaviola; Mimi Yulianti (Badnur Medisa Group, 2022)
The purpose of this study was to determine the level of physical condition of female volleyball athletes at Pekanbaru Pertamina Energi club. This type of research is descriptive research, descriptive research is research that is intended to investigate the circumstances, conditions or other things that have been mentioned, the results of which are presented in the form of a research report. The population in this study were athletes from the Puteri volleyball club Pekanbaru Pertamina Energi Pekanbaru totaling 12 people. The sampling technique used was the total sampling technique. Therefore, the sample in this study were all athletes in the Women's volleyball club PPE (Pekanbaru Pertamina Energi) totaling 12 people. The conclusion of this study is that the level of physical condition of female volleyball athletes at Club Pekanbaru Pertamina Energi is categorized as adequate with an average score of 6.